Factors associated with successful vaginal birth after cesarean section and its outcome in Asella Referral and Teaching Hospital, Ethiopia - Girma, Hulemenash T.; Mekonnen, Hussein; Sendo, Endalew G.; Deressa, Jembere T. (International Journal of Scientific Reports, 2020)
Background: Planned vaginal birth after cesarean section is appropriate for and offered to the majority of women with a singleton pregnancy of cephalic presentation at 37 weeks or beyond. The main purpose of the study was to assess factors associated with successful vaginal birth after cesarean section and its outcome in Asella Referral and Teaching Hospital. Methods: An institutional based case-control study conducted to identify factors associated with successful vaginal birth after cesarean section and its outcome in a two years period. The data was collected from patients’ charts after tracing a patient’s number, a double proportion sampling technique was used to determine sample size using EPI info version 7.1.4.0, and multivariate regression analysis of independent variables associated with successful vaginal birth after cesarean section was performed with unmatched case control. Results: Two hundred eighty-eight (288) mothers with history of one previous cesarean delivery attempted vaginal birth after cesarean section. This study found significant successful vaginal birth after cesarean section in mothers with previous vaginal birth, prior successful vaginal delivery after cesarean section, presented with cervical dilatation more than or equal to 4 cm and intact membrane at admission. Meconium>grade I and duration of labour>481minute negatively affected the success rate but weight did not affect vaginal birth after cesarean outcome. Conclusions: Careful selection of mother is the corner stone of successful vaginal birth after cesarean section with special consideration of gestational age, condition of membrane, and develops national evidence-based clinical practice guidelines for potential implication.